PEMETAAN ZONA DAN RUTE POTENSIAL UNTUK PENERAPAN CARPOOL DI UNIVERSITAS KRISTEN PETRA - Setiawan, Rudy; Debrina Soebagio, Florencia; Gunawan Iskak, Michael (Jurnal Transportasi, 2009)
The use of car by students as a primary mode for commuting to campus has profound effects on campusparking requirements and traffic congestion at peak hours. It is interesting how to reduce the amount ofparking provided and also minimize traffic congestion, but still meet transportation demand. One of thealternative solutions was Campus Transportation Management (CTM), with the purpose of improvingtransportation efficiency by reducing car dependency by changes to other transport modes. Carpool is one ofthe most common and cost effective alternative modes, particularly in areas that are not well served by publictransit. This paper aims to recognize the respond of the students regarding the carpool program and to mappotential zones and routes for the implementation of carpool at Petra Christian University. The result show, ifthe carpool program is be implemented at Petra Christian University, it should begin with several routes themost participants and meet the carpool conditions (participant schedule and characteristics).Keywords: campus transport management, carpool route, carpool matching.